Teacher Interpersonal Communication in Inclusive Education for ADHD Children at Madani Elementary School Cilegon - Pitasari, Dwi Nurina; Marthalena, Marthalena; Asyifa Salama, Asyifa Salama (Al Huwiyah: Journal of Woman and Children Studies, 2026)
This study aims to analyze interpersonal communication strategies employed by teachers toward students with Attention Deficit Hyperactivity Disorder (ADHD) at SD Madani Cilegon, an inclusive elementary school. The research employs a qualitative descriptive approach with a case study method, using observation, in-depth interviews, and documentation as data collection techniques. Findings reveal that teachers implement various interpersonal communication strategies, including empathetic communication, delivery of simple and repetitive instructions, positive reinforcement, strategic seating arrangements, provision of physical activities before learning, and collaboration with parents. Communication barriers encountered include limited teacher time, students' inability to control emotions, and concentration difficulties. To overcome these barriers, teachers apply integrated verbal and nonverbal communication, adjust learning methods, involve parents continuously, and enhance teacher competence through training. The study concludes that effective interpersonal communication plays a crucial role in enhancing focus, reducing impulsive behavior, and facilitating the social-emotional development of ADHD students.